2022
DOI: 10.3390/clinpract12030038
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Progesterone Levels in Female Patients with a History of Idiopathic Scoliosis: A Retrospective Cross-Sectional Study

Abstract: Idiopathic scoliosis is a condition characterized by a three-dimensional curvature of the spine. However, in addition to the spinal curvature, it has also been reported that patients with idiopathic scoliosis can display other abnormal physiologic parameters, such as hormone imbalances, genetic variants, and micronutrient deficiencies. The present study evaluates the salivary progesterone levels from a historical cohort of patients seeking treatment at a single integrative medicine clinic. A group of female pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Although the relationship between progesterone and scoliosis is unclear, this study is consistent with previous findings that female patients with scoliosis show significantly different levels of salivary progesterone compared to non-scoliotic control patients [16]. In adolescence, the chief roles of progesterone are to influence the development of long-term memory, including central pattern generators within the central nervous system [17], as well as mediate the signaling of peak bone mass development as a child nears skeletal maturity [18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the relationship between progesterone and scoliosis is unclear, this study is consistent with previous findings that female patients with scoliosis show significantly different levels of salivary progesterone compared to non-scoliotic control patients [16]. In adolescence, the chief roles of progesterone are to influence the development of long-term memory, including central pattern generators within the central nervous system [17], as well as mediate the signaling of peak bone mass development as a child nears skeletal maturity [18].…”
Section: Discussionsupporting
confidence: 90%
“…It is known that the risk of curve progression occurs chiefly between Risser stages 0-2, where bracing is typically recommended [1]. Morningstar also reported that scoliosis patients show lower salivary progesterone levels compared to non-scoliotic patients [16]. Progesterone serves to help regulate menstrual cycles, and perpetually lower progesterone can impact or delay menarche [22], which is a known risk factor for curve progression over a longer period of time [23].…”
Section: Limitationsmentioning
confidence: 99%
“…Finally, Morningstar and Strauchman [21] observed that female patients without idiopathic scoliosis had 49% more salivary progesterone than that of their scoliosis peers. When examining across the lifespan, their levels remained different until post-menopause.…”
Section: Journal Of Complementary Medicine and Alternative Healthcarementioning
confidence: 96%